Animated Videos Boost Grade IV Short Story Writing Skills: Experimental Study: Meningkatkan Kemampuan Menulis Cerita Pendek pada Siswa Kelas IV melalui Media Video Animasi: Studi Eksperimen Kuantitatif - Firnanda Rizkia Starwati; Kemil Wachidah (Academia Open, 2023)
This study aimed to investigate the influence of animated video media on the short story writing skills of grade IV students at SDN 1 Paciran. The research followed a quantitative experimental approach, utilizing a pre-experimental design with a one-group pretest-posttest design. The population comprised 30 students, and a saturated sampling technique was employed, including all students. Data analysis involved normality tests and paired t-tests. The results of the normality test indicated that the data was normally distributed, as the p-values for both the pretest and posttest were greater than 0.05. The paired t-test analysis revealed a significant improvement in short story writing skills, with a significance value (1-tailed) of 0.000 < 0.05. The findings suggest that the use of animated video media positively influences the development of short story writing skills in grade IV students. This study holds implications for educators and curriculum designers, highlighting the potential of animated video media as an effective tool in enhancing students' writing abilities. Highlights: Interactive learning: The use of animated video media engages students in a dynamic and interactive learning process, enhancing their short story writing skills. Quantitative experimental research: This study employs a quantitative experimental research design to rigorously examine the impact of animated video media on grade IV students' short story writing abilities. Significance of media integration: The findings emphasize the significance of integrating animated video media into the curriculum as a means to foster students' creativity and proficiency in writing short stories. Keywords: animated video media, short story writing skills, grade IV students, quantitative experimental research, pretest-posttest design.